Effects of ursodeoxycholic acid treatment on nutrition and liver function in patients with cystic fibrosis and longstanding cholestasis. Issue 8 (August 1990) - Cotting, J; Lentze, M J; Reichen, J
Abstract : The prevalence of biliary and hepatic diseases is increasing in patients with cystic fibrosis as more of them reach adult life. There is no effective treatment or method of preventing cholestasis in cystic fibrosis, although beneficial effects have been ascribed to the tertiary bile acid, ursodeoxycholate, in other forms of chronic cholestasis. We evaluated prospectively the effects of a six month course of ursodeoxycholate (15-20 mg/kg per day) in eight, mostly adult, patients with cystic fibrosis and chronic cholestasis. Bile acid treatment improved inflammatory activity (average decrease in alanine aminotransferase, 60%, p less than 0.005) and cholestasis (alkaline phosphatase, 47%; p less than 0.01) in all patients. Quantitative liver function, measured by 45 minute sulphobromophthalein retention and by the 14C-aminopyrine breath test, improved in all patients while galactose elimination capacity showed a slight decrease. Patients' nutritional state improved as evidenced by a 1.8 kg weight gain and an increase in muscle mass suggested by a 26% increase in 24 hour urinary creatinine excretion. Steatorrhea was not affected by bile acid treatment. Ursodeoxycholic acid may be beneficial in the treatment of chronic cholestasis in cystic fibrosis by improving liver function and also the patient's nutritional state.